Multimodal imaging of congenital pyriform fossa fistula in children - Zhai, Aiguo; Peng, Xuehua; Guo, Yu; Li, Jian; Shao, Jianbo (Frontiers in Pediatrics, 2023)
Objective: To explore the clinical value of multimodal imaging examinations in the diagnosis of congenital pyriform fossa fistula in children, so as to provide the clues for the early diagnosis and treatment of congenital pyriform fossa fistula. Methods: The clinical and imaging data of 55 children with pyriform fossa fistula diagnosed surgically in our hospital from 2015 to 2018 were analyzed retrospectively. All 55 patients underwent CT scan, of those patients, contrast enhancement CT was performed in 47 cases, MRI was performed in 2 cases and barium esophagography was performed in 41 cases. Results: Among the 55 cases, there were 24 males and 31 females. The age ranged from 11 months to 13 years old, and the median age was 3.8 years old. The lesions of 49 cases (89.1%) were located on the left side, and the imaging of CT showed soft tissue mass in the anterior cervical region, blurred boundary. Ipsilateral thyroid involvement in 50 cases (90.9%), trachea and/or carotid sheath extension in 43 cases (78.2%), abscess formation in 39 cases (70.9%), and pneumatosis in 25 cases (45.5%). CT examination of 22 children after treatment showed linear or tubular low-density shadow in thyroid gland, gas accumulation in anterior cervical region or thyroid, and residual contrast medium partly. 24 cases underwent Barium esophagography during the acute phase. 15 cases (62.5%) showed sinus formation from piriform fossa downward or punctate high-density shadow in anterior cervical region. 2 cases of MRI showed abscess formation in one side of neck and thyroid involvement. Conclusion: Pyriform fossa fistula is most common in the left anterior cervical region and it is closely related to thyroid gland. The plain and enhanced-contrast CT scan be used as the first choice during the infection stage. It is helpful for understanding the location, extent and the structure of surrounding tissue. The preliminary diagnosis of pyriform sinus fistula was according to the imaging features. It provided important basis for clinical diagnosis, and reduced the pain caused by repeated infection or surgical incision and drainage.